Validation and adaptation of a Turkish version of the dietarian identity questionnaire - Damla Gumus; Arife Macit; Senol Demirci; Mevlude Kizil (PLoS ONE, 2025)
Dietarian identity reflects an individual’s cognitive, emotional, and behavioral orientation toward the consumption or avoidance of animal-based foods, including red meat, poultry, fish, eggs, and dairy. This study aimed to adapt and validate the Dietarian Identity Questionnaire (DIQ) for Turkish-speaking populations by establishing its cultural and linguistic suitability and examining dietarian identity profiles among different dietary patterns. The DIQ was adapted into Turkish and administered via a web-based survey to 487 Turkish-speaking adults (Mean age = 28.9 ± 10.7 years; 34.7% male, 64.1% female, and 1.2% non-binary). Participants were categorized as omnivores, vegetarians, or vegans based on self-reported dietary exclusions. Structural validity was assessed using Confirmatory Factor Analysis, while internal consistency, composite reliability, and convergent and discriminant validity were evaluated through Cronbach’s alpha and average variance extracted. Group differences across dietary identity profiles were examined using ANOVA, and interrelationships among the DIQ-Turkish (DIQ-T) subscales were explored through Pearson correlation analysis. The results indicated that the eight-factor DIQ-T demonstrated a strong model fit (χ2 (465) =1841.45, p < 0.001, CFI = 0.924, TLI = 0.914, RMSEA = 0.078, SRMR = 0.050), confirming its structural validity. Reliability analysis indicated high internal consistency across all subscales, and significant differences were observed between omnivores and vegan/vegetarian groups across multiple dimensions (p < 0.001), highlighting distinct psychological and motivational patterns associated with dietarian identity. These findings support DIQ-T as a valid and reliable instrument for assessing dietarian identity, providing a valuable tool for researchers and health professionals investigating dietary behaviors and their potential implications for public health and nutrition interventions.